2011
DOI: 10.1159/000323963
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of the Innate Immune System in Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is a frequent chronic inflammatory skin disease which is often complicated by recurrent microbial superinfections. Genetically based modifications which might have an impact on the innate immune system, such as impairment of the skin barrier, modifications of pattern recognition receptors, deficiency of antimicrobial peptides, antiviral natural killer cells and plasmacytoid dendritic cells, facilitate the entry of allergens and infectious microbes into the skin, where they encounter immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 100 publications
(76 reference statements)
1
32
0
2
Order By: Relevance
“…However, atopic eczema is unlikely to explain the association between atopy and gammaproteobacteria in the present study, given the lack of significant association between atopy and self-reported atopic eczema in our study population (χ 2 = 3.16, P = 0.08). Previous studies have found increased abundance of Staphylococcus on the skin of individuals with atopic eczema (25,26). We found the same, with staphylococci accounting for 5.7% of all sequences in individuals with atopic eczema versus 4.4% in healthy individuals, a non-statistically significant difference (F = 1.53, P = 0.22).…”
Section: Discussionsupporting
confidence: 79%
“…However, atopic eczema is unlikely to explain the association between atopy and gammaproteobacteria in the present study, given the lack of significant association between atopy and self-reported atopic eczema in our study population (χ 2 = 3.16, P = 0.08). Previous studies have found increased abundance of Staphylococcus on the skin of individuals with atopic eczema (25,26). We found the same, with staphylococci accounting for 5.7% of all sequences in individuals with atopic eczema versus 4.4% in healthy individuals, a non-statistically significant difference (F = 1.53, P = 0.22).…”
Section: Discussionsupporting
confidence: 79%
“…However, the function of LCs remains controversial [12][13][14]. In addition, it is not clear up to now, whether LCs are directly activated by allergens or require signals from other cells, such as keratinocytes [15].Keratinocytes are a component of the physical barrier of the skin by formation of tight junctions and production of proteases and antimicrobial peptides [16]. In addition, keratinocytes can secrete proinflammatory cytokines and chemokines and alarmins, such as and thymic stromal lymphopoietin (TSLP) [18], which regulate the influx of inflammatory cells in infection and AD [19].…”
mentioning
confidence: 99%
“…AD is associated with skin barrier abnormalities and a Th2 immune response [13]. AD lesions display lower levels of AMPs than psoriatic plaques [35,36], and are often infected with Staphylococcus aureus , which is associated with AD flares and severity [37,38]. Herpes simplex virus (HSV) infections can also exacerbate AD and Candida species often colonizes atopic skin [37].…”
Section: Prrs As Villains In Primary Skin Disordersmentioning
confidence: 99%